ISBAT WAKAF SEBAGAI UPAYA PERLINDUNGAN HUKUM TANAH WAKAF YANG BELUM BERSERTIFIKAT - Heru Susanto (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Wakaf disputes are found in many places in Indonesia. One of thereasons is that there are many wakaf land that has not been registered(certified) to the authorized official. So it caused that the wakaf landstill do not have certainty and the protection of clear law. This issueencourages legal experts to provide solutions to uncertified wakafland. The solution to provide protection for the wakaf land is theemergence of isbat wakaf as a solution to solve the problems of wakafland that has not been certified.Isbat wakaf aims to provide law protection of wakaf land, justifyingprevious law acts such as waqif, nadzir, and managers, and used asevidence in the certification of waqf objects, giving full advocacy tothe disputed waqf land or legally problematic. Isbat wakaf is theauthority of the Religious Court, this is based on Law no. 14 of 1970amended by Law no. 4 of 2004 on Judicial Power and Law no. 3 of2006 on Amendment to Law no. 7 of 1989 on Religious Courts. InLaw no. 14 of 1970 amended by Law no. 4 of 2004 on Judicial Poweris set forth in Article 2, paragraphs 1 and 2, and Law no. 3 of 2006 onReligious Courts Article 49